LANDASAN DAN ASAS PENGEMBANGAN KURIKULUM - Bradley Setiyadi; Irma Suryani; Resty Framadita (Daiwi Widya, 2022)
AbstractCurriculum development requires strong foundations, which are based on the results of in-depth thoughts and research and are in line with the challenges of the times because the curriculum must have a foundation thus it can stand upright. These foundations are the foundations for the curriculum as its home, therefore it can provide comfort and convenience for students to study and make it a useful product for themselves, their religion, society and country. Each managed curriculum must be able to be developed and perfected to suit the rate of development of science and technology and the developing society. This paper applied a method in the form of theoretical studies regarding the principles and foundations of curriculum development. These theories were summarized and the threads were sought thus a discussion of the principles and foundations of curriculum development can be put forward.Keywords: Curriculum Development, Curriculum Principles, Curriculum Foundation